Inhibition of nonstructural protein 15 of SARS‐CoV‐2 by golden spice: A computational insight - Singh, Rahul; Bhardwaj, Vijay K.; Purohit, Rituraj (Cell biochemistry and function, 2022)
The quick widespread of the coronavirus and speedy upsurge in the tally of cases demand the fast development of effective drugs. The uridine‐directed endoribonuclease activity of nonstructural protein 15 (Nsp15) of the coronavirus is responsible for the invasion of the host immune system. Therefore, developing potential inhibitors against Nsp15 is a promising strategy. In this concern, the in silico approach can play a significant role, as it is fast and cost‐effective in comparison to the trial and error approaches of experimental investigations. In this study, six turmeric derivatives (curcuminoids) were chosen for in silico analysis. The molecular interactions, pharmacokinetics, and drug‐likeness of all the curcuminoids were measured. Further, the stability of Nsp15‐curcuminoids complexes was appraised by employing molecular dynamics (MD) simulations and MM‐PBSA approaches. All the molecules were affirmed to have strong interactions and pharmacokinetic profile. The MD simulations data stated that the Nsp15‐curcuminoids complexes were stable during simulations. All the curcuminoids showed stable and high binding affinity, and these curcuminoids could be admitted as potential modulators for Nsp15 inhibition. Significance statement We implemented advanced computational approaches to highlight the inhibitory mechanism of bioactive molecules of turmeric against nonstructural protein 15 (Nsp15) of SARS‐CoV‐2. In this study, we reported that the turmeric compounds could interact effectively with Nsp15 of SARS‐CoV‐2 and inhibit its further progression. The reported molecules from turmeric could be developed as potential inhibitors against the Nsp15 of SARS‐CoV‐2.